Analisis Semiotika Pada Film “Shigatsu Wa Kimi No Uso” Episode 3 Adegan 5 - Hidayat, Mohammad Syarif; Luthfie, Muhammad; Kusumadinata, Ali Alamsyah (CommLine, 2022)
The anime series Shigatsu wa Kimi no Uso is an anime adapted from a manga (Japanese comic) with the same title as the main character named Arima. Based on the anime series shows, that there are implied meanings that can be analyzed by semiotic analysis as in episode 3 scene 5. Therefore, this study aims to analyze the meaning contained in episode 3 scene 5 of the anime series Shigatsu wa Kimi no Uso with the formula the problem "Does the anime series Shigatsu wa Kimi no Uso episode 3 scene 5 contain the meaning of Arima's attitude change?" This study used a descriptive qualitative research approach and semiotic analysis in this study uses Charles Sanders Prierce's theory of semiotic analysis in which there were three elements in meaning, namely sign, object, and interpretant. This research focused on visual analysis and analysis of Arima's dialogue. There were eight signs that can be taken for analysis. Based on the eight signs, it means a change in Arima's attitude as shown in Arima's shift from the dark side to the light, the movement of a cherry blossom petal from the dark side to the light side, Arima's dialogue that refuses to play the piano which ultimately accepted the offer to play the piano and several signs which was indicated by a meaning that was in harmony with Arima's change in attitude. So it can be concluded that in the Shigatsu wa Kimi no Uso anime series episode 3, scene 5, there was an implied meaning that was in line with the change in attitude had shown by Arima as the main character.